Faktor-Faktor Penggerak Kinerja Karyawan di PT. Home Credit Indonesia Jakarta Selatan: Disiplin Kerja Dan Motivasi Kerja - Dewi Ulfah Arini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is one of the most crucial factors in achieving organizational success, and it is often influenced by internal factors such as the physical work environment and work motivation. This study aims to determine whether the physical work environment and work motivation have a positive and significant effect, either partially or simultaneously, on employee performance at PT Home Credit Indonesia, South Jakarta. The research adopts a quantitative approach with a causal associative method. The population consists of 90 employees, and the sampling technique used is saturated sampling. Data was collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 22. The findings of this study indicate that both the physical work environment and work motivation have a positive and significant impact on employee performance. This suggests that when employees feel comfortable and supported by their physical surroundings, and are driven by strong internal or external motivation, their productivity and work quality improve. It highlights that performance is influenced not only by skills but also by environmental and psychological factors. The implication for companies is to invest in improving workplace conditions and implementing motivation-enhancing strategies to optimize employee output and overall organizational effectiveness in a sustainable and measurable way.